Kepemimpinan Transformasional dan Inovasi pada Generasi Z: Peran Efikasi Diri Kreatif - Thomas Irwan Kristanto; Fanny Martdianty (Universitas KH. Abdul Chalim Mojokerto, 2025)
Amid mounting bureaucratic complexity and performance demands, public organizations increasingly rely on employees’ innovative work behavior (IWB) to remain adaptive and effective. This study examines the effect of transformational leadership on IWB among Generation Z employees in a State Financial Management Organization, focusing on the mediating role of creative self-efficacy. Data were collected through a survey of 351 respondents using purposive sampling and analyzed using Structural Equation Modeling (SEM) via LISREL. The results reveal that while transformational leadership has a significant direct effect on IWB, its indirect effect through creative self-efficacy is stronger. This underscores the importance of employees’ belief in their creative capabilities as a key psychological mechanism linking leadership style to innovative behavior. Theoretically, this study contributes to the leadership and innovation literature in Indonesia’s public sector context, particularly concerning the underexplored Generation Z workforce. Practically, the findings highlight the need to foster work environments that enhance creative self-efficacy and promote leadership that is not only visionary but also psychologically empowering.